2023
DOI: 10.18267/j.aip.215
|View full text |Cite
|
Sign up to set email alerts
|

Use of Data Mining for Analysis of Czech Real Estate Market

Ilya Tsakunov,
David Chudán

Abstract: This paper analyses data from the real estate market domain. The data were scraped from the bezrealitky.cz portal. The analysis looks at both sales and rental data. A total of 3546 records and 54 attributes were obtained. A basic overview of the data was performed using exploratory data analysis where some basic characteristics of the data were identified, such as the average price of sold and rented flats. More specific results were obtained by applying data mining methods such as regression (linear regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Experimental studies have demonstrated the superiority of these enhanced algorithms in effectively clustering categorical datasets [53,54]. K-modes clustering has increasingly been applied in recent research across diverse fields, playing a crucial role in analysing categorical data for tasks such as market segmentation, customer profiling, and pattern recognition [49,[55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have demonstrated the superiority of these enhanced algorithms in effectively clustering categorical datasets [53,54]. K-modes clustering has increasingly been applied in recent research across diverse fields, playing a crucial role in analysing categorical data for tasks such as market segmentation, customer profiling, and pattern recognition [49,[55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%